HEALTH-SEEKING BEHAVIOR (A PHENOMENOLOGICAL STUDY ON HEALTH-SEEKING BEHAVIOR AMONG THE PARENTS WITH UNDER-FIVE AGE CHILDREN IN SUMPIUH SUB DISTRICT) - Agung Kurniawan (UNIVERSITAS SEBELAS MARET (UNS), 2022)
UNICEF for Indonesia reported that one child dies before their fifth birthday every three minutes anywhere in Indonesia. The factor causing the high child mortality rate is not only non-evenly distributed health facility but also parents’ health behavior. The objective of research was to analyze the health-seeking behavior among the parents with under-five age children by considering resources, thought and feeling, culture, and personal references dimensions in affecting the health-seeking behavior. This study was a qualitative research with phenomenological approach. Techniques of collecting data used were observation, in-depth interview, and documentation. The respondents were taken using maximum variation sampling technique by considering the accurate representation of total population. To validate the data, triangulation was used, and an interactive model was used in data processing. This research built on Social Behavior paradigm, Talcott Parsons’ social action, stating that every actor has an objective to be achieved in which he/ she has an alternative way to use, but they are limited by situation, condition, value, norm, and other idea affecting their decision making. The result of research and discussion showed that there were two health-seeking behaviors taken by parents in seeking treatment for their children encountering the health problem without being limited by their economic status and education level. Firstly, parents would treat their children themselves, using both traditional medicines and drugs they bought from store or pharmacy. Secondly, parents looked for treatment directly from medical officers (either Midwife or Puskesmas) when their children suffered from either mild or severe health disease. Keywords: Health-seeking Behavior, Parents, Under-Five Age AbstrakUNICEF untuk Indonesia melaporkan bahwa satu anak meninggal sebelum ulang tahun kelima mereka setiap tiga menit di mana pun di Indonesia. Faktor penyebab tingginya angka kematian anak tidak hanya fasilitas kesehatan yang tidak merata tetapi juga perilaku kesehatan orang tua. Tujuan penelitian adalah untuk menganalisis perilaku mencari kesehatan di antara orang tua dengan anak-anak di bawah lima tahun dengan mempertimbangkan sumber daya, pemikiran dan perasaan, budaya, dan dimensi referensi pribadi dalam mempengaruhi perilaku mencari kesehatan. Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomenologis. Teknik pengumpulan data yang digunakan adalah observasi, wawancara mendalam, dan dokumentasi. Responden diambil dengan menggunakan teknik maximum variation sampling dengan mempertimbangkan representasi akurat dari total populasi. Untuk memvalidasi data, triangulasi digunakan, dan model interaktif digunakan dalam pemrosesan data. Penelitian ini dibangun di atas paradigma Perilaku Sosial, Tindakan sosial Talcott Parsons, menyatakan bahwa setiap aktor memiliki tujuan yang ingin dicapai di mana dia memiliki cara alternatif untuk digunakan, tetapi mereka dibatasi oleh situasi, kondisi, nilai, norma, dan ide lain yang mempengaruhi pengambilan keputusan mereka. Hasil penelitian dan diskusi menunjukkan bahwa ada dua perilaku mencari kesehatan yang dilakukan oleh orang tua dalam mencari pengobatan untuk anak-anak mereka yang menghadapi masalah kesehatan tanpa dibatasi oleh status ekonomi dan tingkat pendidikan mereka. Pertama, orang tua akan merawat anak-anak mereka sendiri, menggunakan obat-obatan tradisional dan obat-obatan yang mereka beli dari toko atau. Kedua, orang tua mencari perawatan langsung dari petugas medis (baik Bidan atau Puskesmas) ketika anak-anak mereka menderita penyakit kesehatan ringan atau berat. Kata Kunci: Perilaku Mencari Kesehatan, Orang Tua, Usia Balita